International criminal law - Cassese, Antonio (Oxford University Press, 2003)
This new book by Cassese provides a clear and concise account of the principles governing international crimes and an outline of international criminal trials. Adopting a combination of the classic common law and more theoretical approaches to the subject, it expounds the fundamentals of both substantive and procedural international criminal law, providing a theoretical framework to all the rules, principles, concepts, and legal constructs key to the subject. It also offers extensive treatment of the most significant traditional and novel cases in English, as well as unique English translations of a selection of relevant judgments in Dutch, French, German, Italian, and Spanish, demonstrating the historical and human dimensions of such cases, and providing effective illustration of the practical problems encountered by criminal courts